Marriage Matters (UCL Press, 2025)
Statistics show steep declines in formal partnerships in Uganda. Yet marriage, commitment, love and relationships still matter profoundly to individuals, family, generations, friends and wider society. What does it mean to be married or not married in contemporary Uganda?